Improving Students Academic Writing Quality by Using ICT Online Tools at English Tadris Study Program in IAIN Curup - Hidayah, Jumatul; Prihantoro, Prihantoro; Apriani, Eka; Patil, Atul Bansilal; Obaid, Ahmed J.; Durgayan, Alesa; Zulihi, Zulihi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
The complexities of academic writing need the efficient use of ICT tools to assist English students in writing. The current study focused on the above discussion. The purpose of this study was to investigate the usage of ICT tools for English academic writing, as well as their usefulness. 50 students from IAIN Curup's English department were recruited to participate. This study's data were gathered using an explanatory sequential mixed-method design via questionnaires, interviews, and student artifacts. Data were examined using both quantitative and qualitative criteria. In terms of ICT tools, this study discovered that students used a variety of online resources to improve the quality of their academic writing, including citation tools, search engines, editing tools, translation tools, monolingual and bilingual dictionaries, and a bilingual concordancer. In terms of the usefulness of ICT tools, this study discovered that online resources benefited students in a variety of ways when conducting their English academic writing assignments. As a result, using editing software, students were able to maintain proper grammar and sentence flow. The translation tool was another great resource that enabled students to broaden their vocabulary in order to speak successfully in a range of situations and registers. Students can learn more by utilizing search engines on their own. They could uncover statistics to back up their writing. In a nutshell, the use of digital tools improved the quality of students' English academic writing.